Strategic Innovation in Improving 21st Century Competencies at SMPN 46 Surabaya - Musafa’ah, Ani; Arbi, Anggun Purnomo; Kasinta, Shofia Permata (Gudang Jurnal Multidisiplin Ilmu, 2024)
Today's education faces the challenge of preparing students with competencies that are relevant to the demands of the times. This research aims to explore innovative strategies in improving 21st Century competencies at SMPN 46 Surabaya. The research method involved classroom observation, interviews with teachers, and document analysis. Findings show that project-based learning, the use of interactive technology, cooperative learning models, and student-centered approaches are effective in developing 21st Century competencies. In addition, simulation activities, innovative curriculum development, special extracurricular programs, and continuous teacher training also play an important role. The conclusions emphasize the need for inclusive and innovative learning approaches in dealing with the demands of modern education. The findings provide a strong foundation for the development of effective learning strategies to improve students' 21st Century competencies in the future.